THE INFLUENCE OF WORK FACILITIES, WORK DISCIPLINE, AND COMPETENCE ON EMPLOYEE PERFORMANCE OF CV. SUKSES INTERMODA PERKASA PENUKAL ABAB LEMATANG ILIR (PALI) REGENCY - Madani, Aulya; Edy Liswani; Randy Hidayat; Bora Alviolesa (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to determine the influence of work facilities, work discipline and competence on the employee performance of CV. Success Intermoda Perkasa (PALI) Regency, both jointly and individually. This type of research uses associative research. The population is 140 employees and the sample is 60 employees. Sampling used the Disproportionate Stratified Random Sampling technique. The data used is primary data and secondary data. The analysis technique uses Multiple Linear Regression, Hypothesis Testing F and t, and Coefficient of Determination. The results of Multiple Linear Regression show that there is a positive influence between work facilities, work discipline and competence on the employee performance of CV. Success Intermoda Perkasa (PALI) Regency. The results of the F test show that there is a significant influence of work facilities, work discipline, and competence on employee performance, and the results of the t test show that there is a significant influence of work facilities on employee performance, there is a significant influence of work discipline on employee performance, and there is a significant influence of competence on employee performance. The results of the Coefficient of Determination show that work facilities, work discipline and competence contribute 79.5% to changes in the employee performance of CV. Success Intermoda Perkasa (PALI) Regency